2020
DOI: 10.1002/hed.26556
|View full text |Cite
|
Sign up to set email alerts
|

Parotid gland stem cells: Mini yet mighty

Abstract: Background: Our aim was to evaluate the correlation between the radiation doses to parotid gland (PG) stem cells and xerostomia. Methods: Patients diagnosed with head and neck cancer (HNC) were retrospectively evaluated, and xerostomia inventory (XI) was applied to these patients. PG stem cells were delineated on the treatment planning CT, and the mean doses to the PG stem cells calculated. Results: The total test score and mean doses to bilateral PGs were significantly correlated (r = .34, P = .001), and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The parotid glands, the submandibular glands, the oral cavity, and specific regions of the parotid glands were investigated. 8,15,[38][39][40][41][42][43][44][45][46] The next step is prioritization of relevant OARs for treatment optimization, currently often determined using a prospective or retrospective cohort study. However, a major issue in elucidating the role of a potential structure is collinearity between doses to different OARs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The parotid glands, the submandibular glands, the oral cavity, and specific regions of the parotid glands were investigated. 8,15,[38][39][40][41][42][43][44][45][46] The next step is prioritization of relevant OARs for treatment optimization, currently often determined using a prospective or retrospective cohort study. However, a major issue in elucidating the role of a potential structure is collinearity between doses to different OARs.…”
Section: Discussionmentioning
confidence: 99%
“…However, aside from dose to the contralateral SCR region, dose to other OARs, pretreatment xerostomia, and additional clinical risk factors (eg, age, tumor location and classification, and administration of systemic therapy) are also relevant for the development of xerostomia. 8,15,[38][39][40][41][42][43][44][45][46] Therefore, the development of normal tissue complication probability models for the different xerostomia endpoints, considering the role of the SCR region in addition to other risk factors, will contribute to prioritizing the sparing of different OARs and might be an aid for the selection of treatment techniques, such as adaptive radiation therapy or proton therapy. 10,11 Sparing subvolumes of the parotid glands Finally, in other studies, associations between dose to parotid gland subvolumes and parotid function were also investigated (ie, salivary flow and/or xerostomia).…”
Section: Sparing the Contralateral Stem Cell Dense Region To Prevent Xerostomiamentioning
confidence: 99%
“…Nevertheless, the incorporation of voxel-dose parameters does not appear to significantly improve the model’s predictive ability relative to conventional dosimetric parameters [ 28 ]. Moreover, Sari et al recently reported that that D mean to parotid stem cells (located inside the Stenson duct perimeter) had a comparable ability to predict xerostomia than did D mean to entire parotids [ 47 ]. Lastly, the performance of the proposed models was not validated in an independent external cohort, which would have allowed them to demonstrate their robustness and transportability to other settings.…”
Section: Discussionmentioning
confidence: 99%
“…The current clinical approach to minimizing the risk of xerostomia is preservation of salivary function by minimizing the dose to the parotid glands in treatment planning. Several studies have indicated that post-radiotherapy parotid gland function and xerostomia are better predicted by dose to regions or spatial features of the dose distribution [110][111][112][113][114][115]. As mentioned above, a region adjacent to the dorsal edge of the mandible was identified as the best predictor of post-treatment function [110].…”
Section: Parotid Gland Major Ductsmentioning
confidence: 99%